EU DEMOGRAPHIC CHARACTERISTICS: GLOBAL MEGATRENDS AND OPPORTUNITIES FOR THE RETAIL SECTOR - Олена Сергієнко; Світлана Прокопович; Марина Татар; Олександр Білоцерківський; Олександр Чернов; Олександр Кизлюк (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article proposes the complex of economic and mathematical models for assessment and analysis of the peculiarities of the demographic situation in the EU countries for the formation of recommendations on improving the retail trade sector development adapted to each group of countries. Key global megatrends such as population ageing, declining share of the working-age population, increasing migration flows, urbanization, digitalization and consumer behaviour changing, and increasing environmental awareness are analyzed. The study highlights the challenges and opportunities these changes present for the retail sector. A cluster-based model is developed to categorize countries into distinct demographic profiles, facilitating targeted retail strategies. The research employs factor analysis and multidimensional assessment methods to quantify the influence of demographic indicators, incorporating both stimulating and disincentive effects on retail market dynamics. This structured approach enables the design of differentiated business strategies, ensuring optimal market positioning and consumer engagement. The research also includes the examination of meta-spatial business collaborations as a crucial mechanism for retail adaptation. Particular focus is given to the adaptation of business models to cater to the needs of an ageing population, and the development of inclusive product assortments for multicultural communities. The results allow us to identify countries, in which it is optimal to develop youth-driven digital engagement models, senior-friendly shopping environments, and culturally inclusive retail ecosystems. The study underscores the necessity of aligning demographic data with emerging retail innovations to foster economic adaptability in an evolving global landscape. Companies can use demographic insights to form business collaborations with suppliers, brands, and marketing agencies that complement their audience, ensuring more effective partnerships and increased profitability. Based on demographic characteristics, government authorities can effectively regulate the trade sector, and ensure the availability of goods for the population. The findings underline the importance of integrating demographic analysis into strategic planning to enhance the retail sector's resilience.